Determinan Kualitas Laba Studi Pada Financial Times Stock Exchange (FTSE)ASEAN STAR PERIODE 2014-2015 - Denny Saputera; Nida Laila Laila (Jurnal Manajemen, 2019)
Earnings quality is the quality of earnings information presented in the financial statements which reflects the actual performance of the firm. The quality is reflected in the investors responses on earnings publication. In this research, earnings quality is measured by earnings response coefficient. This study aimed to investigate the effect of leverage, firm performance (ROA) and the liquidity on earnings quality is measured using the Earnings Response Coefficients. This study was performed on companies listed in Financial Times Stock Exchange (FTSE)ASEAN STAR 2014-2015 period. Samples were obtained by 110 by purposive sampling method. The technique of data analysis used is multiple linear regression analysis. Firm performance measured by the return on assets (ROA), and liquidity measured by current ratio (CR). The result showed that leverage  had influence on earnings quality. Meanwhile, firm performance and liquidity had no effect on earnings response coefficient (ERC). Key Words: Leverage, Firm Performance, Liquidity and Earnings Response Coefficient